Risk factors for maternal anaemia and low birth weight in pregnant women living in rural India: a prospective cohort study - Ahankari, Anand S.; Myles, Puja R.; Dixit, J.V.; Tata, Laila J.; Fogarty, Andrew W. (Elsevier, 2017)
Objective: The aim of this prospective study was to estimate the prevalence and risk factors for maternal anaemia and low birth weight in pregnant women living in Maharashtra state, India.